Comparison of CAD/CAM manufactured implant-supported crowns with different analyses - Elif Yeğin; Mustafa Hayati Atala (SpringerOpen, 2020)
Abstract Background Present study compared the failure load of CAD/CAM-manufactured implant-supported crowns and the stress distribution on the prosthesis-implant-bone complex with different restoration techniques. Methods The materials were divided into four groups: group L-M: lithium disilicate ceramic (LDS, monolithic), group L-V: LDS ceramic (veneering), group ZL-M: zirconia-reinforced lithium silicate ceramic (ZLS, monolithic), group ZL-V: ZLS ceramic (veneering). Crown restorations were subjected to load-to-failure test (0.5 mm/min). Failure loads of each group were statistically analyzed (two-way ANOVA, post hoc Tukey HSD, α = 0.05). Finite element analysis (FEA) was used to compare the stress distribution of crown restorations. Results Group L-M had the highest failure load (2891.88 ± 410.12 N) with a significant difference from other groups (p < 0.05). Although there was a significant difference between group ZL-M (1750.28 ± 314.96 N) and ZL-V (2202.55 ± 503.14 N), there was no significant difference from group L-V in both groups (2077.37 ± 356.59 N) (p > 0.05). Conclusions The veneer application had opposite effects on ceramics, increased the failure load of ZLS and reduced it for LDS without a statistically significant difference. Both materials are suitable for implant-supported crowns. Different restorative materials did not influence the stress distribution, but monolithic restorations reduced the stress concentration on the implant and bone.